Protein digestibility of soybean: how processing affects seed structure, protein and non-protein components - Vinny Kohli; Siddhartha Singha (Discover Food, 2024)
Abstract Protein digestibility is a key indicator of dietary protein quality because the amino acids present in a protein food may not be available to an organism for nutrition and health unless they are digested. In spite of being a good source of protein, Soybean seed has limited digestibility mainly in their whole form. In this paper, we highlight the factors that affect the digestibility of soybean proteins like the quantity, structure, and distribution of the kinetically stable proteins plus the anti-nutritional compounds in soybean seeds. Furthermore, factors such as seed coat thickness and composition, cellular integrity, and seed hydration can also impact the protein digestibility of soybeans. It was found that wet thermal treatments like cooking along with operations such as fermentation, grinding and germination have a more favourable effect on hydrolysis of soybean proteins than dry-heat treatments such as roasting. Also, all processing operations have the ability to reduce the anti-nutritive compounds to varying degrees, ensuring the safety and increased digestibility of the soybean. The current review exhibits the potential processing methods for facilitating mechanical disintegration and protein hydrolysis of soybean seeds. Hence, the insights gained from this review can be used to understand the mechanism by which various processing methods enhance the protein digestibility of soybean seeds. The findings of this review indicate the necessity to carefully adjust processing conditions to preserve nutritional quality, reduce anti-nutritional components to safe levels, and optimize both protein digestibility and palatability of whole soybean seeds.